Transcranial direct current stimulation for the treatment of obsessive-compulsive disorder? A qualitative review of safety and efficacy. (January 2019) - Rachid, Fady
Highlights: Obsessive-compulsive disorder is a highly disabling psychiatric disorder characterized by recurrent, obsessions and compulsions. 60% of patients respond partially or not to first-line treatments for OCD consist of selective serotonin reuptake inhibitors and to cognitive-behavioral therapy. This paper reviewed the literature on the safety and efficacy of transcranial direct current stimulation for the treatment of obsessive-compulsive disorder and found that it might help reduce symptom of obsessive-compulsive disorder. Future well-designed sham-controlled studies are needed to confirm the short and long-term safety and efficacy of transcranial direct current stimulation for the treatment of obsessive-compulsive disorder. Abstract: Obsessive-compulsive disorder (OCD) is a highly disabling psychiatric disorder characterized by recurrent obsessions and compulsions. It has a lifetime prevalence of 1–3% in the general population and commonly has a chronic course. First-line treatments consist of selective serotonin reuptake inhibitors and cognitive-behavioral therapy but up to 60% of patients respond partially or not at all to these treatments. This paper reviewed the literature on the safety and efficacy of transcranial direct current stimulation (tDCS) for the treatment of obsessive-compulsive disorder and discussed future directions for research and clinical application. Criteria for inclusion were open or controlled studies on tDCS and OCD that used validated rating scales along with well-described stimulus parameters. In the majority of the limited number of published studies, most patients with treatment-resistant obsessive-compulsive disorder had either moderate or marked benefit with this technique different stimulation targets, sometimes sustained for many months. This technique might be efficacious in the treatment of obsessive-compulsive disorder, although it is difficult to draw definitive conclusions about its efficacy, future well-designed sham-controlled studies are needed to confirm the safety and efficacy of tDCS for the treatment of this condition.